2017
DOI: 10.4038/cjs.v46i3.7444
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of <em>Cylindrospermopsis raciborskii</em> (Cyanobacteria) in Sri Lanka

Abstract: Sri Lanka is a tropical continental island which consists of 103 natural rivers and over ten thousand man-made lakes. Majority of these water resources are known to be contaminated with different types of toxigenic cyanobacteria making water unsuitable for human and animal consumption. Cylindrospermopsis raciborskii, a toxin producing tropical cyanobacterium, recently recorded at high abundances in lentic waters of the country. This species is highly adaptive and exhibit different morphotypes: straight, coiled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…According to our observations, the spatial distribution pattern of CYN in Mahakanadarawa reservoir is approximately uniform while in Nachchaduwa it showed slight accumulation toward the direction of the South (Figures 4b and 4d). Although we did not observe any of the CYN-producing cyanobacterial species in either of the reservoirs, Wanigatunge et al (2014) and Yatigammana and Perera (2017) have reported the presence of potential CYN-producing cyanobacterial species Cylindrospermopsis raciborskii in Nachchaduwa. However, in this study, we did not observe C. raciborskii or any other CYNproducing species probably due to two reasons, one is the presence of very low densities of such filaments at the time of sampling due to their disappearance.…”
Section: And Cyn Cyanotoxins and Their Spatial Distributioncontrasting
confidence: 78%
See 1 more Smart Citation
“…According to our observations, the spatial distribution pattern of CYN in Mahakanadarawa reservoir is approximately uniform while in Nachchaduwa it showed slight accumulation toward the direction of the South (Figures 4b and 4d). Although we did not observe any of the CYN-producing cyanobacterial species in either of the reservoirs, Wanigatunge et al (2014) and Yatigammana and Perera (2017) have reported the presence of potential CYN-producing cyanobacterial species Cylindrospermopsis raciborskii in Nachchaduwa. However, in this study, we did not observe C. raciborskii or any other CYNproducing species probably due to two reasons, one is the presence of very low densities of such filaments at the time of sampling due to their disappearance.…”
Section: And Cyn Cyanotoxins and Their Spatial Distributioncontrasting
confidence: 78%
“…At the same time, Mycrocystis was identified as a dominant genus in northern dry zone reservoirs (Jayawardana et al 1998). Several later research reported toxigenic genera Cylindrospermopsis raciborskii as the dominant cyanobacterial community in several northern dry zone reservoirs and its co-occurrence with Microcystis only in Unnichchai tank (Wanigatunge et al 2014;Kulasooriya 2017 andYatigammana andPerera 2017). Further, several other toxin-producing cyanobacteria such as Planktolyngbya, Pseudoanabaena, Anabaena aphanizomenoides (Silva and Wijeyaratne 1999), Phormidium, Oscillatoria (Liyanage et al 2014) and Lyngbya (Shihana et.…”
Section: And Cyn Cyanotoxins and Their Spatial Distributionmentioning
confidence: 98%
“…Thus, considering the toxic nature of CYN on human health, the World Health Organization (WHO) established a provisional guideline limit for CYN of 2 µg/L in drinking water (WHO, 2003;SLSI, 2013) and 0.02 µg/kg of body weight/day as the Tolerable Daily Intake (TDI) for humans (Guzman-Guillen et al, 2014). Recently, there have been increasing reports on the number and the intensity of blooms in reservoirs in the North Central, North East, and Uva Provinces of Sri Lanka (Madhushankha et al, 2013;Yatigammana & Perera, 2017;Manage, 2019). Further, scientific research has revealed contamination of the majority of drinking water reservoirs by toxin-producing cyanobacterium M. aeruginosa, Cylindrospermopsis sp., Anabaena sp.…”
Section: September 2022mentioning
confidence: 99%
“…These "cyanotoxins" are usually either hepatotoxic or neurotoxic in pathology and have been related to several cases of human sickness and death, as well as various occurrences of animal mortality (Falconer, 2005; Kuiperpolonicum, P. willei, P. volzii and P. aciculiferum have been identified as common freshwater species (Niese et al, 2007). Among them, Peridinium aciculiferum, known to produce a biological toxin, has already been recorded from Sri Lankan drinking water reservoirs (Yatigammana and Perera, 2017;Yatigammana et al, 2011;Sethunge & Pathmalal,2010;Idroos et al, 2017).…”
Section: Cyanobacteriamentioning
confidence: 99%